Factors influencing adults who participate in a physical activity coaching intervention: a theoretically informed qualitative study. Issue 8 (4th August 2022) - Barrett, Stephen; Begg, Stephen; O'Halloran, Paul; Breckon, Jeff; Rodda, Kane; Barrett, Gabrielle; Kingsley, Michael
Abstract : Objective: Behaviour change interventions targeting changes in physical activity (PA) can benefit by examining the underlying mechanisms that promote change. This study explored the use of the Capability, Opportunity, Motivation and Behaviour (COM-B) model and the Theoretical Domains Framework (TDF) to code and contextualise the experiences of participants who completed a PA coaching intervention underpinned by motivational interviewing and cognitive–behavioural therapy. Design: Semistructured interviews were conducted with a purposive sample of participants. Setting: Interviews were conducted in a tertiary hospital in regional Victoria, Australia. Participants: Eighteen participants who completed a PA coaching intervention were interviewed. The participants were recruited into the coaching intervention because they were insufficiently physically active at the time of recruitment. Results: Thirteen (72%) participants were women and the average age of participants was 54 (±5) years. Four participant themes mapped directly onto five components of the COM-B model, and ten of the TDF domains. Increases in PA were influenced by changes in motivation and psychological capability. The autonomy-supportive PA coaching intervention helped to evoke participants' own reasons (and motives) for change and influenced PA behaviours. Participants reflected on their own social and/or professional strengths, and used these skills to set appropriate PA goals and action plans. The structure of the PA coaching intervention provided clarity on session determinants and a framework from which to set an appropriate agenda. Relational components (eg, non-judgemental listening, collaboration) were continually highlighted as influential for change, and should be considered in future behaviour change intervention design. Conclusions: We demonstrate the beneficial effect of using theory-informed behaviour change techniques, and delivering them in a style that promotes autonomy and relatedness. The views of participants should be a key consideration in the design and implementation of PA coaching interventions Trial registration number: ACTRN12619000036112. Post-results analysis.